A Method for the Chromatic Aberration Correction of a Laser Time of-Flight Mass Analyzer. Issue 3 (June 2016) - Sysoeva, Elizaveta A.; Sysoev, Alexander A.
The new ion-optical system of the laser time-of-flight (TOF) mass spectrometer on the basis of two tandem wedge-shape reflectors has been offered and implemented. A new method of correcting chromatic aberration by the ion energy was proposed that used a wire electrode unit with adjustable potentials. This unit allows one to adjust the local TOF of the ions in a narrow energy range ±1–2% within the total ion packet with an energy spread of ±20%. The method reduces the duration of the ion packets by up to 1.5 ns, which enables us to obtain the restriction of resolution at a level not worse than R ∼ 10, 500 for a TOF of ∼35 μs. The aim of the project is to increase the separation of isobaric ions to improve the limit of detection of the laser TOF-MS for the analysis of high-purity samples.